2021
DOI: 10.1158/1940-6207.capr-20-0140
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Modulation by Vitamin D and Calcium in the Morphologically Normal Colorectal Mucosa of Patients with Colorectal Adenoma in a Clinical Trial

Abstract: Increased COX-2 and decreased 15-hydroxyprostaglandin dehydrogenase (15-HPGD) expression promote prostaglandin-mediated inflammation and colorectal carcinogenesis. Experimental studies suggest that vitamin D and calcium may inhibit these pathways, but their effects on colorectal tissue COX-2 and 15-HPGD expression in humans are unknown. We tested the effects of supplemental vitamin D (1,000 IU/day) and/or calcium (1,200 mg/day) on COX-2 and 15-HPGD expression in the morphologically normal rectal mucosa from 62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…As yet mentioned, PGE2 is degraded by the 15-PGDH enzyme (encoded by the HPGD gene), and its dysfunction promotes the pathogenesis of several diseases. It plays a critical role in the regulation of inflammation, and a reduction in its expression is associated with the development of this pathological condition [ 226 ]. 15-PGDH activity promotes cardiac fibrosis, even in the infarcted heart, owing to PGE2 degradation; it has been shown that its deletion promotes cardiac recovery and reduces the fibrosis of the heart, too.…”
Section: Prostanoidsmentioning
confidence: 99%
“…As yet mentioned, PGE2 is degraded by the 15-PGDH enzyme (encoded by the HPGD gene), and its dysfunction promotes the pathogenesis of several diseases. It plays a critical role in the regulation of inflammation, and a reduction in its expression is associated with the development of this pathological condition [ 226 ]. 15-PGDH activity promotes cardiac fibrosis, even in the infarcted heart, owing to PGE2 degradation; it has been shown that its deletion promotes cardiac recovery and reduces the fibrosis of the heart, too.…”
Section: Prostanoidsmentioning
confidence: 99%
“…1,25(OH) 2 D 3 reduces the protumorigenic effect of PG E 2 in prostate cancer cells by inhibiting COX-2 and so decreasing the levels of PG E 2 and two PG receptors (EP2 and FP) [ 286 ]. Importantly, vitamin D and calcium favorably modulate the balance of expression of COX-2 and 15-hydroxyPG dehydrogenase, its physiological antagonist, in the normal-appearing colorectal mucosa of patients with colorectal adenoma [ 287 ]. Vitamin D enhances the tumoricidal activity of NK cells and macrophages [ 288 , 289 ].…”
Section: Mechanisms Introductionmentioning
confidence: 99%
“…Our findings suggest a similar but weaker pattern of effect modification by DBP2 for calcium supplementation on adenoma risk. In this group’s previous biomarker study, calcium supplementation, relative to placebo, statistically significantly reduced cyclooxygenase-2 colorectal tissue expression but only among individuals with the DBP2 isoform. DBP2 is associated with lower circulating DBP concentrations, which may increase parathyroid hormone secretion and calcium absorption, possibly leading to stronger supplemental calcium effects …”
Section: Discussionmentioning
confidence: 68%
“…Second, DBP2 is associated with approximately 2- to 4-fold lower 25(OH)D binding affinity, which may increase vitamin D bioavailability, and 2- to 3-fold higher vitamin D target-gene expression induction by 25(OH)D in vitro relative to DBP1s/DBP1f. Third, in a subset of this trial’s participants, vitamin D 3 relative to placebo statistically significantly decreased colorectal tissue expression of cyclooxygenase-2, an inflammation-related biomarker of risk for colorectal cancer, but only among those with the DBP2 isoform …”
Section: Discussionmentioning
confidence: 91%